MAKTAB YOSHIDAGI O‘ZBEKZABON BOLALAR OG‘ZAKI NUTQINI MAIN METODOLOGIYASI ASOSIDA O‘RGANISH - Hamidova Gulrux Axmat qizi, (TADQIQOTLAR, 2026)
Annotation. This article presents the experience of studying the oral narrative speech  of  school-aged  (grades  1–5)  Uzbek-speaking  children  based  on  the internationally  standardized  MAIN  (Multilingual  Assessment  Instrument  for Narratives)  methodology.  In the  study,  the  speech of 11  participants  was collected using  the  "Cat  Story"  visual  stimulus  and  analyzed  according  to  psycholinguistic indicators (MLU, TTR, syntactic complexity, speech rate). The article focuses on the methodological aspects of applying the MAIN instrument to the Uzbek language.